Carbonyl Compounds in Salted Cod.: II. Separation and Identification of Volatile Monocarbonyl Compounds from Heavily Salted Cod - Yurkowski, M.; Bordeleau, M.A. (Journal of the Fisheries Research Board of Canada, 1965)
Volatile monocarbonyl compounds were isolated from heavily salted cod (Gadus morhua) as the 2,4-dinitrophenylhydrazones. These compounds were separated by thin-layer chromatography first into classes and then according to chain length. n-Alkanals C 1–5 and n-alk-2-enals C 5–6 were conclusively identified. n-Alkanals C 8,10 and n-alk-2-enals C 4,7,8 were tentatively identified. An unknown compound corresponding to n-hexanal, except in the melting point, was isolated. Formaldehyde, and to a lesser extent, acetaldehyde and propanal, were the major monocarbonyls present in salted cod.